2014
DOI: 10.1093/gerona/glu065
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-A -Mediated Vasoconstriction During Exercise With Advancing Age

Abstract: The endothelin-1 vasoconstrictor pathway contributes to age-related elevations in resting peripheral vascular tone primarily through activation of the endothelin subtype A (ET(A)) receptor. However, the regulatory influence of ET(A)-mediated vasoconstriction during exercise in the elderly is unknown. Thus, in 17 healthy volunteers (n = 8 young, 24±2 years; n = 9 old, 70±2 years), we examined leg blood flow, mean arterial pressure, leg arterial-venous oxygen (O2) difference, and leg O2 consumption (VO2) at rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 48 publications
2
54
0
Order By: Relevance
“…This attenuation in exercise-induced hyperemia has been attributed to various age-related alterations in the vascular mechanisms that regulate muscle perfusion (5,40). The lower Q L in the old compared with the young participants observed in our experiments supports these earlier observations (Fig.…”
Section: Aging and Exercise-induced Peripheral Hemodynamicssupporting
confidence: 90%
“…This attenuation in exercise-induced hyperemia has been attributed to various age-related alterations in the vascular mechanisms that regulate muscle perfusion (5,40). The lower Q L in the old compared with the young participants observed in our experiments supports these earlier observations (Fig.…”
Section: Aging and Exercise-induced Peripheral Hemodynamicssupporting
confidence: 90%
“…When considering that blood flow is determined by the integration of central (cardiac output, mean arterial pressure) and peripheral hemodynamics (vascular conductance or resistance) and the multitude of factors that regulate these processes during exercise, it is unlikely that a single molecule will encompass the properties of a master regulator. Indeed, thus far, this notion is supported by many elegant investigations utilizing pharmacological dissection of specific vasodilatory pathways [68, 1318]. However, when considering the overall goal of increased blood flow during exercise, to match oxygen delivery and oxygen demand, it becomes evident that even minor modifications in blood flow in the intact human may have significant consequences in terms of physical performance [19].…”
Section: Introductionmentioning
confidence: 99%
“…A subset of these data focusing on the role of ET A receptor inhibition and blood flow regulation during basal conditions and knee extension exercise in these study participants has been reported previously [35]. Study participants were not taking any prescription medications and were free of overt cardiovascular disease.…”
Section: Methodsmentioning
confidence: 99%
“…Upon arrival at the laboratory, body mass and height were recorded, and the right femoral artery was catheterized (18-gauge central venous catheter; Arrow International, Reading, Pennsylvania, USA) using the Seldinger technique. After the catheter placement, study participants rested for ~30 min and then performed knee extension exercise as previously described for a separate investigation [35]. After knee extension exercise, study participants rested for at least 60 min to ensure the return to baseline central and peripheral hemodynamics, including LBF, mean arterial pressure (MAP), and heart rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation